Mercado de trabalho em empresas de tecnologia no Brasil: Desafios e oportunidades - Barbosa, Munyse Barros (2023)
In the current scenario, characterized by mass layoffs in the labor market, this study aims to analyze the behavioral and sociodemographic patterns of those who were laid off by technology organizations from January 2022 to July 2023. Initially the development of the research was carried out by bibliographical study with the objective of understanding the main concepts related to the labor market, skills, abilities, and people analytics. Documentary research was conducted to obtain secondary data available in electronic media such as LinkedIn and layoff sites, with the objective of mapping information such as skills and area of activity of the dismissed professional so that subsequently it will be possible to analyze the profile of these professionals. As a data analysis technique, descriptive statistics are used to describe the profile of impacted professionals. As main results, it appears that a large part of the dismissed professionals are men, white, with completed higher education and that the vast majority of them work in the area of User Experience (UX). This result corroborates several studies that point to inequality in the IT market and the difficulty for minorities in entering it. As a technological product, we propose the creation of an infographic, with development tips, training and how to get back into the market, aimed at professionals in the information technology field.